1990
DOI: 10.1002/anie.199013971
|View full text |Cite
|
Sign up to set email alerts
|

GeII and SnII Complexes of [2.2.2]Paracyclophane with Threefold Internal η6 Coordination

Abstract: 191 X-ray structure analysis of the [22]coproporphyrin I1 Zb space group P2,/n. a = 828.1(5), b = 2619.5(6), c = 1028.7(6) pm, fl = 100.30(2)'. Z = 2, four-circle diffractometer CAD4 (Enraf-Nonius) (Cu,,, L = 154.178 pm, graphite monochromator), 3561 measured reflections. Further details of the crystal structure investigation may be obtained from the Fachinformationszentrum Karlsruhe, Gesellschaft fur wissenschaftlichtechnische Information mbH. W-7514 Eggenstein-Leopoldshafen 2 (FRG), on quoting the depository… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 23 publications
2
59
1
Order By: Relevance
“…Two of the coordinated toluene molecules (A and C, see Figure 3) show a positional disorder, which was resolved by using a split model with a 6:4 occupation of both sides. In contrast to the previously reported molecular structure of the [2.2.2]paracyclophane-Sn II complex 7 [22] with a threefold h 6 coordination of the arene rings and Sn À C separations between 281.7(5)-307.5(6) pm, the coordination of the Sn atom in cation 5 is not symmetric. That is, the arene rings A and C are significantly closer to the central Sn atom than ring B.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Two of the coordinated toluene molecules (A and C, see Figure 3) show a positional disorder, which was resolved by using a split model with a 6:4 occupation of both sides. In contrast to the previously reported molecular structure of the [2.2.2]paracyclophane-Sn II complex 7 [22] with a threefold h 6 coordination of the arene rings and Sn À C separations between 281.7(5)-307.5(6) pm, the coordination of the Sn atom in cation 5 is not symmetric. That is, the arene rings A and C are significantly closer to the central Sn atom than ring B.…”
Section: Resultscontrasting
confidence: 79%
“…[21] The synthesis of homoleptic tin(II) complexes void of additional coordination by a counter anion was achieved through the synthesis of complex 7 by using [2.2.2]paracyclophane as ligand. [22] Only the use of the weakly coordinating perfluorinated tetraarylborate, however, allowed the abdication of the chelating effect of the cyclophane and permitted the isolation of the tris-toluene complex 5. À anion and tin cation 5 are clearly separated; the shortest Sn À F distance is 326.1 pm, which is somewhat shorter than the sum of the van-der-Waals radii (364 pm).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the synthesis of 1, a complex of cryptand [2.2.2] with Ge 2+ , highlighted the possibility of isolating reactive germanium cations using electron-rich macrobicyclic molecules to stabilize the cation with numerous weak donor acceptor interactions, rather than with any discrete two-center-two-electron bonds. [7,8] Although it is well established that cryptands can sequester metallic cations, 1 was the first example of a cryptand nonmetal cationic inclusion complex and represented a novel approach to isolating lighter p-block cations.…”
mentioning
confidence: 99%
“…33 85 Schmidbaur et al found that such a macrocyclic ligand (cyclophane) can also stabilize germanium and tin cations. 34 However, the use of macrocyclic ligands for realizing p-block cations was extensively increased since Baines' report of a germanium(II) dication encapsulated in [2.2.2]cryptand. 35 In the 90 following years, a range of macrocyclic ligands like crown ethers, cryptands, azamacrocycles etc.…”
mentioning
confidence: 99%